Investigating the molecular mechanism of traditional Chinese medicine for the treatment of placental syndromes by influencing inflammatory cytokines using the Mendelian randomization and molecular docking technology - Huang, Shan; Cai, Shuangming; Ling, Lin; Zhang, Wenni; Xiao, Huanshun; Yu, Danfeng; Zhong, Xuan; Tao, Pei; Luo, Yiping (Frontiers in Endocrinology, 2024)
Introduction: Placental syndromes, which include pregnancy loss, preterm birth, gestational diabetes mellitus (GDM), and hypertensive disorders in pregnancy (HDP), have a strong association with disorder inflammatory reactions. Nonetheless, the exact causal relationship has not been established. This study aims to investigate the causal relationship between placental syndromes and inflammatory cytokines utilizing Mendelian randomization (MR). Additionally, we examined the interaction between small molecular compounds derived from traditional Chinese medicine and inflammatory cytokines using molecular docking method. Methods: After obtaining the data of inflammatory cytokines and placental syndromes, as well as establishing single nucleotide polymorphisms (SNPs), we employed the inverse variance weighted (IVW) method to assess the causal relationship. We also accessed the heterogeneity and the horizontal pleiotropy of these data. The "ClusterProfiler" R package was utilized for Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and Gene Ontology (GO) term analyses. The protein-protein interaction (PPI) network was constructed using STRING database. AutoDock Vina software was used for molecular docking, and Discovery Studio 2019 was used for visualization purposes. Results: We found that the growth regulated oncogene A (GROA) and interleukin-9 (IL-9) were associated with the development of pregnancy hypertension, whereas interleukin-10 (IL-10) and hepatocyte growth factor (HGF) were linked to the occurrence of preeclampsia. Moreover, there were correlations observed between interleukin-18 (IL-18), IL-10, macrophage colony-stimulating factor (MCSF), and platelet-derived growth factor BB (PDGFbb) in cases of chronic hypertension combined with pregnancy (CHP). Additionally, macrophage migration inhibitory factor (MIF) exhibited a connection with GDM, and TNF related apoptosis inducing ligand (TRAIL) demonstrated a causal relationship with preterm birth. It is plausible to suggest that interleukin-1β (IL-1β) might contribute to the promotion of pregnancy loss. All of the binding free energy values of small molecular compounds with inflammatory cytokines were below −5.0 kcal/mol. Furthermore, all of the RMSD values were less than 2. Conclusions: GROA, IL-1β, IL-9, IL-10, IL-18, MIF, MCSF, HGF, PDGFbb and TRAIL were found to be causally associated with placental syndromes. Molecular docking analysis revealed that small molecular compounds, such as puerarin, magnolol, atractylenolide I, paeoniflorin, tumulosic acid and wogonin, are closely bound to these inflammatory cytokines.